A FEW MORE PROPERTIES OF SUM AND INTEGRAL SUM GRAPHS - Vilfred, V (IndoMS, 2014)
The concepts of sum graph and integral sum graph were introduced by Harary [7], [8]. A sum graph is a graph whose vertices can be labeled with distinct positive integers so that the sum of the labels on each pair of adjacent vertices is the label of some other vertex. Integral sum graphs have the same definition except that the labels may be any integers. Harary [7], [8], gave examples of all orders of sum graphs Â and integral sum graphs , nÃŽN. The family of integral sum graph was extended by Vilfred (see [14]), and in this paper, we obtain a few properties of sum and integral sum graphs and two new families of integral sum graphs.DOI :Â http://dx.doi.org/10.22342/jims.20.2.172.148-159